Fears and affections of the inquisitorial practice Legitimation and spiritual control through the celebrated auto-da-fe lime the year 1639 - Morales Ceron, Carlos (2011)
By means of the present I study it is sought to understand, like one of the most important mechanisms used by the tribunal of the Inquisition and the authorities virreinales to establish his identity and to assure his control on the population’s intention to the auto-da-fes. The inquisitorial procedure himself I characterize principally to promote insecurity and distrust between inhabitants and accuseds to promote fear and delation among themselves, while during the interrogations it was sought to reestablish a means of asymmetric confidence between the judges with the defendant. With the auto-da-fes it was sought to implicate the one-act population public of reaffirmation of the faith that you demonstrated the colonial and the Holy Office State’s power to them.